Analysis of syariah quantitative screening norms among Malaysia syariah-compliant stocks / Pok Wee Ching … [et al.] - Pok, Wee Ching; Haniff, Mohd Nizal; Ameer, Rashid; Poshakwale, Sunil (Research Management Institute (RMI), 2012)
The purpose of this study is to investigate whether Malaysian Syariahcompliant quantitative screening adopts criteria, which can be considered more liberal than those used by the DJIM, S&P and FTSE Syariah index providers, and also to assess the financial health of the sample companies. To do these, a sample of 477 Syariah-compliant firms were tested using the financial ratios, namely, liquidity ratio, interest ratio, debt ratio and non-permissible income ratio used by these world-leading index providers. The results showed that fewer companies (12.16%) qualify under the DJIM criteria and even more companies (63.10%) qualify under the FTSE criteria. The reasons for this difference are (1) the use of different formulae to calculate the ratio (2) the use of different thresholds and (3) the different emphases applied by the world index providers. The results of the financial health screen show that the majority of the Syariah-compliant companies are financially healthy.